Illness and Fall in Albert Camus - Montero Bosch, David (Logos. Anales del Seminario de Metafísica, 2016)
This article focuses on the theme of illness in Albert Camus. Special emphasis is placed on his last published novel, La Chute. The issue of disease is usually focused in relation to death and finitude both in literature and philosophy. This article focuses on the relation between the existential experience of illness and the decay of the plenitude of life. The case of Albert Camus is especially significant for his chronical illness and because disease has a prominent place in his literary works. Here La Chute is chosen because it offers a great richness of interpretative levels unparalleled in other camusian works. Two different reading levels are proposed. The distinction and the analysis of these two levels will allow for more nuanced view of the relationship of the author to his work and of the controversy about the social role of the intellectual. The conclusion of this article differs both from the critics who only consider the novel in relation to the polemic with Jean-Paul Sartre, and those who interpret it as a disguised confession.
Keywords: Camus; illness; nihilism; hedonism; dominance; violence; Dostoevsky; confession; Nietzsche